Development of transgenic Musa acuminata cv. ‘Berangan’ with pathogenesis-related (PR10) gene conferring tolerance to Fusarium oxysporum f. sp. cubense tropical race 4 / Nadiya Akmal Baharum - Nadiya Akmal , Baharum (2017)
Fusarium wilt is caused by a type of soil-borne fungus, Fusarium oxysporum f. sp. cubense (Foc) that colonizes banana roots and causes blockage in the transportation of the necessary nutrients through xylems. The disease greatly hinders the production of banana worldwide. Although various measures have been executed, such as introduction of new breeding programs and disease control, none was found to be effective in combating this disease. Hence, the development of disease-resistant banana cultivars is vital. In this study, an anti-fungal gene called pathogenesis-related (PR) 10 was isolated from wild-type banana, Musa acuminata ssp. malaccensis (MaPR-10). Using rapid amplification of cDNA ends (RACE) technique, the full-length DNA and cDNA sequences of the gene were revealed to be 949 bp and 773 bp, respectively. MaPR-10 has a 176-bp-intron which is spanned in between two exons with 5‘ untranslated region (UTR) and 3‘UTR of 62 bp and 228 bp, respectively. MaPR-10 encodes a putative protein of 160 amino acids with a predicted molecular mass of 17.46 kDa and an isoelectric point of 5.42. The predicted MaPR-10 protein contains a functional domain, called Betv1-like, and a prominent conserved glycine-rich, P-loop motif of GxGxxG. MaPR-10 was successfully introduced into a commercial banana cultivar ‗Berangan‘ via co-cultivation of Agrobacterium tumefaciens and embryogenic cells suspension. A total of 17 putative transgenic lines were recovered on the hygromycin-selection medium and 11 of them tested positive for transgene integration following PCR analysis. Plantlets of line labeled 19 (Line-19) demonstrated the most rapid in-vitro propagation and thus were selected for further analysis. Line-19 plantlets possibly contain a single copy of MaPR-10 and successfully over-express the transgene relative to the untransformed controls. To investigate the effect of MaPR-10 in enhancing tolerance against Foc race 4 (FocR4) C1 HIR, the baseline disease response was first established using wild-type ‗Berangan‘ plants. Using root-dipping technique, it was found that inoculation of two-month-old plants in C1 HIR suspension culture containing 1 x 106 spores/ml for two hours was able to produce consistent disease symptoms. Wild-type ‗Berangan‘ plants exhibited wilting and yellowing leaf symptoms as early as one week after inoculation. Scoring of leaf symptoms index (LSI) and rhizome discoloration index (RDI) was performed in the 5th week post-inoculation to evaluate the disease severity of the infected plants. Wild-type ‗Berangan‘ was found to be highly susceptible to C1 HIR isolate with LSI and RDI scores of 4.3 and 6.0, respectively. In the bioassay evaluation of Line-19 plants, about 30% showed a delay in wilting and yellowing leaf symptoms, which were observed two weeks after inoculation. In addition, Line-19 plants harboring MaPR-10 were found to be highly susceptible to C1 HIR isolate with LSI and RDI scores of 3.4 and 6.1, respectively. Based on this observation, Line-19 plants may have acquired tolerance against the infection as shown by the delayed disease progression. For future studies, disease evaluation of other transgenic lines as well as introduction of more than one anti-fungal gene can be considered to achieve a better resistance trait.